Rancang Bangun Sistem Informasi Manajemen Event Berbasis Mobile - Aditya Teguh Pratama; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Organizing events is one of the activities affected by the pandemic. The compulsory social distancing makes coordination between committee events difficult because it must be done boldly, therefore the role of technology is needed by creating an event management information system. The purpose of studying this research is to implement the design results of the Management Information System to simplify and assist in management. The method used is the Waterfall method with the JavaScript programming language and the React Native framework. This system was developed using MongoDB which is useful for providing database services, then used with the system using GraphQL. Furthermore, testing is carried out using the white box and black box methods with the results of the system testing being declared to have passed the test. This application is expected to be able to feed all event organizers in terms of event management including committees, committees, and assignments.